PENGUJIAN USABILITY ANTARMUKA APLIKASI BRAILLE SMART PADA SISWA TU¬NANETRA - Rakhma Shafrida Kurnia; Ema Utami; Hanif Al Fatta (Informasi Interaktif, 2017)
The visually impaired is is a person who can not use his eyes as the primary senses to obtain information on the environment (Nawawi, 2010).  Visual impairment in a person, causing the visually impaired will have limitations. The limitations are as follows: (1) obtain information and new experiences, (2) interaction with the environment, and (3) mobility. The development of communication technology, especially on a handheld cell phone that starts with a keypad, developed into a flat-screen smartphone makes it difficult to use by the visually impaired. B-SMART application comes with the concept of Virtual Braille Keyboard,  application of the concept of Braille as navigation and input so that the blind people can use the touch screen smartphone. This study aims to evaluate the application of B-SMART by measuring the level of effectiveness, efficiency and user satisfaction of the B-SMART mobile applications. The method of analysis in this study using Cognitive Walkthrough  combined with Quistionairre for User Interface Satisfaction (Quis). The test results showed the effectiveness of B-SMART application amounted to 85.0%, the efficiency level is 42.7% and the satisfaction of respondents was 77.1%. The results show that there is a problem faced by respondents when using the application to complete the task scenario seen from the effectiveness of 85% and an efficiency of 42.7%. The test results are discussed in the Focus Group Discussion and used as the basis of the recommendations on the improvement of the interface of B-SMART.Keywords : Visually impaired, Mobile Application, User interface, Usability, Cognitive Walkthrough